2020
DOI: 10.3390/ijms21249423
|View full text |Cite
|
Sign up to set email alerts
|

Spheroid-Like Cultures for Expanding Angiopoietin Receptor-1 (aka. Tie2) Positive Cells from the Human Intervertebral Disc

Abstract: Lower back pain is a leading cause of disability worldwide. The recovery of nucleus pulposus (NP) progenitor cells (NPPCs) from the intervertebral disc (IVD) holds high promise for future cell therapy. NPPCs are positive for the angiopoietin-1 receptor (Tie2) and possess stemness capacity. However, the limited Tie2+ NPC yield has been a challenge for their use in cell-based therapy for regenerative medicine. In this study, we attempted to expand NPPCs from the whole NP cell population by spheroid-formation ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…The classic and common culture conditions are based on 2D culture and normoxic environment [13][14][15]. In this research, we primarily wanted to compare the impact of chemical treatments on the Tie2+ NPPCs population [16,17]. For this reason, the cells were cultured within a normoxic environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The classic and common culture conditions are based on 2D culture and normoxic environment [13][14][15]. In this research, we primarily wanted to compare the impact of chemical treatments on the Tie2+ NPPCs population [16,17]. For this reason, the cells were cultured within a normoxic environment.…”
Section: Discussionmentioning
confidence: 99%
“…Cells' morphology was quantified by using ImageJ v1.53c software on the microscopic pictures, using "cell body circularity" functionality [28,29]. An example of how the cells' outlines were defined by manual segmentation can be found in a previous study [17].…”
Section: Visualisation Of Cell's Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…As such, a need exists to optimize or develop new culture methods that enable the maintenance of Tie2-expressing NPPC. A variety of studies have investigated different approaches to improve culture conditions [ 26 , 29 , 30 , 31 , 32 ] or isolation methods [ 22 ] to increase the number of Tie2-expressing cells. Bovine-derived NP cell studies have suggested a synergistic beneficial role of fibroblast growth factor 2 (FGF2; also known as basic fibroblast growth factor) and a hypoxic culture environment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Tie2 + NPPC was originally discovered by their formation of spheroid colony-forming units (CFUs) within a methylcellulose semi-solid medium [ 21 ]. Moreover, Zhang et al reported a high colony formation rate and Tie2 positivity rate by using an ultra-low attachment T75 flask [ 30 ]. Similarly, Guerrero et al recently found enhanced Tie2 + NPPC maintenance by employing a 3D environment of alginate-beads with enhanced pluripotency markers.…”
Section: Introductionmentioning
confidence: 99%